2015
DOI: 10.1177/1350650115571994
|View full text |Cite
|
Sign up to set email alerts
|

An extended ultrasonic time-of-flight method for measuring lubricant film thickness

Abstract: An extended ultrasonic time-of-flight (TOF) method is proposed for measuring the thickness of lubricant film. Based on the spectrum analysis method of superimposed pulses, the extended TOF determines the travel time of ultrasonic wave and subsequently the film thickness in frequency domain. The method extends the measurable range of the original TOF method to the lubricant films of superimposed reflected pulses, which usually processed by the resonance model. The extended TOF gives another interpretation to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…It is seen that the sum in Equation (4) equals −R 1 R l (t) and further equals the sum in Equation (3). With this realisation, it is seen that T l (t) is given by Equation (6).…”
Section: The Acoustic Model Used For Adaptive Calibrationmentioning
confidence: 80%
See 1 more Smart Citation
“…It is seen that the sum in Equation (4) equals −R 1 R l (t) and further equals the sum in Equation (3). With this realisation, it is seen that T l (t) is given by Equation (6).…”
Section: The Acoustic Model Used For Adaptive Calibrationmentioning
confidence: 80%
“…Ultrasound transducers are a promising sensor technology because they are considered to be noninvasive. They are considered noninvasive primarily due to the high penetrability of ultrasonic waves, which allows for convenient placement of the ultrasound transducers without disturbing the system structure, design, and lubrication properties [1][2][3]. The most common use of ultrasound transducers in lubrication film monitoring is ultrasound reflectometry.…”
Section: Introductionmentioning
confidence: 99%
“…for the overall complex reflection coefficient of the three-layer system [24]. From this equation, one can also derive simplified reflection models like Liquid Spring Model [22,23,25,31], Resonance Model [17] or the Time-of-Flight Method [27]. Each of them is only valid for a limited range of thicknesses and frequencies, respectively.…”
Section: Analytical Modelmentioning
confidence: 99%
“…For example, the time-and frequency-related investigation of ultrasound reflected at a thin layer is a typical approach with regard to tribological systems. In this field, it is used to determine the thickness of lubricant films, some of which are less than 100 µm thick, such as those found in ball bearings [21][22][23][24][25][26][27]. However, this approach has not yet been applied to medical problems where rough, non-geometric surfaces as well as very inhomogeneous, highly damping materials with not exactly known probabilities and strong individual deviations are found [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…However, by analyzing the time interval between two echoes, it is found that the minimum point phenomenon is caused by the definite time interval between two echoes instead of the resonance phenomenon [29]. Focusing on these two different explanations about the formation mechanism of the minimum point, the superposition principle of waves has been used to analyze the minimum point phenomenon.…”
Section: ) Frequency-domain Modelsmentioning
confidence: 99%